The Cambridge handbook of One Health and the law : existing frameworks, intersections and future pathways / edited by Katie Woolaston, Jane Kotzmann. - Woolaston, Katie, 1983-; Kotzmann, Jane (Cambridge University Press, 2025)
This handbook is essential for legal scholars, policymakers, animal and public health professionals, and environmental advocates who want to understand and implement the One Health framework in governance and law. It explores how One Health - an approach integrating human, animal, and environmental health - can address some of the most pressing global challenges, including zoonotic diseases, biodiversity loss, climate change, and antimicrobial resistance. Through detailed case studies, the book demonstrates how One Health is already embedded in legal and policy frameworks, evaluates its effectiveness, and offers practical guidance for improvement. It compares One Health with other interdisciplinary paradigms and existing legal frameworks, identifying valuable lessons and synergies. The book concludes by mapping a transformative path forward, showing how One Health can be used to fundamentally reshape legal systems and their relationship with health and sustainability. This is an invaluable resource for anyone seeking innovative, equitable, and sustainable solutions to global health challenges.